2007
DOI: 10.1007/s12029-008-9027-x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Rates of Missed Diagnosis for Colonoscopy, Barium Enema, and Flexible Sigmoidoscopy in 379 Patients with Colorectal Cancer

Abstract: Failure rates for colonoscopy, barium enema, and flexible sigmoidoscopy were 9%, 20%, and 50%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Current recommendations for CRC screening emphasize optical endoscopy (i.e. sigmoidoscopy or colonoscopy) [ 2 ] or fecal immunochemical test for blood (FIT) [ 3 ]. However, there are several problems encountered when endoscopy is used as a first-line screening tool.…”
Section: Introductionmentioning
confidence: 99%
“…Current recommendations for CRC screening emphasize optical endoscopy (i.e. sigmoidoscopy or colonoscopy) [ 2 ] or fecal immunochemical test for blood (FIT) [ 3 ]. However, there are several problems encountered when endoscopy is used as a first-line screening tool.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study by Somasekar et al ,16 found that 56 (10%) patients with a diagnosis of CRC had undergone barium enema (5%) or colonoscopy (5%) in the preceding 5 years. Another study by Frenette and Strum17 reported a failure of diagnosis in 60 (16%) patients who had undergone colonoscopy, barium enema or flexible sigmoidoscopy in the preceding 3 years. Our results are significantly lower than the cohorts of Somasekar and Frenette (p<0.005, χ 2 test), and suggest a low ‘miss-rate’ for CRC with these investigations within our unit.…”
Section: Discussionmentioning
confidence: 99%
“…Ensemble CNN model with explainable AI for the classification of gastrointestinal cancer year timeline [8]. Nonetheless, a study conducted by [9] put forward that cognitive and technological issues contribute to significant diagnostic errors, despite the effectiveness of traditional screening procedures.…”
Section: Plos Onementioning
confidence: 99%
“…However, if gastrointestinal cancers are detected in their early stages, the survival rate becomes higher in the five year timeline [ 8 ]. Nonetheless, a study conducted by [ 9 ] put forward that cognitive and technological issues contribute to significant diagnostic errors, despite the effectiveness of traditional screening procedures.…”
Section: Introductionmentioning
confidence: 99%